Pendampingan peningkatan nilai infak terhadap akuntanbilitas infak masjid di desa bojong kulur gunung putri bogor - Herawati, Heny; Pangeran, Pangeran; Sunardi, Sunardi; Waskito, Meindro; Fauzizah, Adillah; khairiyah, Anisah (Gapenas Publisher, 2022)
Mosques are a non-profit religious institution. Mosques are not only places of worship but also places for social activities. In today's mosque management, it is not only about the physical activities of the mosque but also more complex matters, such as mosque financial management. Financial management of mosques is also very important because the funds obtained from mosques come from infaq and sodagoh funds which must be recorded in an accountable manner and reported to the community regularly. However, there are still many mosques that have not implemented systematic financial management. This community service aims to implement a financial management system for non-profit institutions. Training on mosque financial management was carried out with partners from the Mosque Prosperity Council (DKM) and women administrators of the Al Muhajirin Taklim Council (MTM). Training participants are people who are active as administrators. The training will be held at the Muhajirin Mosque which is located at Villa Nusa Indah 1 Bojong Kulur. Implementation of the service begins with gathering information regarding participants' financial management needs, followed by the importance of creating a dawn alms program as input for mosque infaq funds, and creating a financial reporting program. After the training is carried out, the next stage is to review the extent to which the material provided can be implemented by the participants.